The Effect Of Giving Bread Yeast And Urea Fertilizer On Rotifer Growth Rate (Brachiounus plicatilis) - Naning Dwi Sulystyaningsih; Khilal Aditya; L. Achmad Tan Tilar WSK; Nuri Muahiddah (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2023)
Types of natural food that is good and has a very high nutritional value can support the life of fish larvae is Rotifer (Banchionus plicatilis). Rotifers have the ability to develop well in a relatively short time. The research objective was to identify and describe the effect of bread yeast and urea fertilizer on the growth rate of rotifers (B. plicatilis). The research method used a completely randomized design, 4 treatments (P) with 3 replications, with a total of 12 experimental units. The treatment consists of: P0: No feed; P1: Baker's Yeast 150 mg/l; P2: Urea Fertilizer 150 mg/l; and P3: Combination of Baker's Yeast and Urea Fertilizer 150 mg/l and cultured for 9 days. Based on the results of observing rotifers for 9 days, the application of baker's yeast and urea fertilizer had a significant effect on the rotifer growth rate (K), specific growth (SGR), population density and self-replication time (DT). The best treatment is giving baker's yeast 150 mg/l. Water quality management affects the level of success and success in the Rotifer cultivation period.